Towards 4th generation biomaterials: a covalent hybrid polymer–ormoglass architecture. Issue 37 (2nd September 2015) - Sachot, N.; Mateos-Timoneda, M. A.; Planell, J. A.; Velders, A. H.; Lewandowska, M.; Engel, E.; Castaño, O.
Abstract : Nanostructured hybrid materials are an excellent option to create extracellular matrix-like environments for cell fate control in bone tissue engineering. Abstract : Hybrid materials are being extensively investigated with the aim of mimicking the ECM microenvironment to develop effective solutions for bone tissue engineering. However, the common drawbacks of a hybrid material are the lack of interactions between the scaffold's constituents and the masking of its bioactive phase. Conventional hybrids often degrade in a non-homogeneous manner and the biological response is far from optimal. We have developed a novel material with strong interactions between constituents. The bioactive phase is directly exposed on its surface mimicking the structure of the ECM of bone. Here, polylactic acid electrospun fibers have been successfully and reproducibly coated with a bioactive organically modified glass (ormoglass, Si–Ca–P2 system) covalently. In comparison with the pure polymeric mats, the fibers obtained showed improved hydrophilicity and mechanical properties, bioactive ion release, exhibited a nanoroughness and enabled good cell adhesion and spreading after just one day of culture (rMSCs and rEPCs). The fibers were coated with different ormoglass compositions to tailor their surface properties (roughness, stiffness, and morphology) by modifying the experimental parameters. Knowing that cells modulate their behavior according to the exposed physical and chemical signals, the development of this instructive material is a valuable advance in the design of functional regenerative biomaterials.